2017
DOI: 10.1111/cbdd.12970
|View full text |Cite
|
Sign up to set email alerts
|

MD simulations and multivariate studies for modeling the antileishmanial activity of peptides

Abstract: Leishmaniasis, a protozoan-caused disease, requires alternative treatments with minimized side-effects and less prone to resistance development. Antimicrobial peptides represent a possible choice to be developed. We report on the prospection of structural parameters of 23 helical antimicrobial and leishmanicidal peptides as a tool for modeling and predicting the activity of new peptides. This investigation is based on molecular dynamic simulations (MD) in mimetic membrane environment, as most of these peptides… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…In fact, on biological evaluation, decoralin exhibited a significant broad-spectrum antimicrobial activity and moderate mast cell degranulation and leishmanicidal activities, but showed virtually no hemolytic activity. A synthetic analog with C-terminal amidation showed much more potent activity in all the biological assays [11], and NMR experiments demonstrated its amphipathic α-helix secondary structure [28].…”
Section: Chemical and Biological Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, on biological evaluation, decoralin exhibited a significant broad-spectrum antimicrobial activity and moderate mast cell degranulation and leishmanicidal activities, but showed virtually no hemolytic activity. A synthetic analog with C-terminal amidation showed much more potent activity in all the biological assays [11], and NMR experiments demonstrated its amphipathic α-helix secondary structure [28].…”
Section: Chemical and Biological Characterizationmentioning
confidence: 99%
“…However, results obtained with model peptides suggested that helicity is more important to peptide activity on zwitterionic membranes than to permeabilization of the negatively charged ones [74]. Structural information on solitary wasp venom peptides is mainly based on CD data; to the best of our knowledge, NMR experiments were carried out just for EMP-AF [24] and decoralin [28]. Accumulating information obtained from the interaction of solitary wasp venom peptides with model membranes by NMR would help establishing a database with an increased confidence level.…”
Section: Physicochemical Properties and Secondary Structurementioning
confidence: 99%
“…We carefully chose the mutation sites based on the wild‐type primary sequence and amino acid positions in the amphipathic secondary structure acquired by Dec‐NH 2 in hydrophobic environments, as described by Guerra et al. . The substitutions were made by replacing amino acids from the original sequence by Arg (charged residue), Phe and Trp (aromatic hydrophobic amino acids).…”
Section: Characterization and Theoretical Physicochemical Properties mentioning
confidence: 99%
“… A) Secondary structure of Dec‐NH 2 proposed by Guerra et al. . Colored in blue are positions substituted which led to increased anti‐plasmodial activity (N‐terminus); B) Dec‐NH 2 helical wheel, where yellow circles represent hydrophobic residues, blue circles show the positively charged residues, and purple circles represent the polar uncharged residues; and C) CD spectra were recorded after four accumulations at 20 °C using a 0.5 mm path length quartz cell between 190 and 260 nm at 50 nm min −1 with a band width of 0.5 nm.…”
Section: Characterization and Theoretical Physicochemical Properties mentioning
confidence: 99%
“…NMR data were obtained in the absence of micelles and similarity decreases over simulation time, Figure S10: The conformations centroids of the less populated clusters after hierarchical clustering of the predicted structures of cationic peptides with activity against Gram negative bacteria. References [11,12,14,15,16,18,19,20,21,22,31,33,34,37,44,45,46,47,48,49,50,51,52,53,54,55,56,57,58,59,60,61,62,63,64,65,66,67,68,69,70,71,72,73,74,75,76,77,78,79,80,81,82,83,84,85,86,87,88,89,…”
mentioning
confidence: 99%